Peran Negara terhadap Konflik SARA di Indonesia : Kajian Historis - Suyahmo, Suyahmo (Universitas Terbuka, 2022)
Abstract. This study aims to analyze the government's role in the SARA conflict in Indonesia. This research method used historical concept studies. Primary historical data sources and secondary data sourced from books and articles. The results of this study reveal a comparison of the government's role since the transition period, namely the period after changing the leadership of the new era to the democratic era. The dark transition period have shifted to become dynamic, due to the increasing level of democratic awareness. The conclusion of this study is the potential for horizontal conflict in Indonesia as a plural country as high risk, and become a powerful time bomb. The sentiment of identities are getting sharper because there are political elites interests that encourage the patronage of civil society and the media.